The invasive alien leaf miner Cameraria ohridella and the native tree Acer pseudoplatanus: a fatal attraction? - Péré, Christelle; Augustin, Sylvie; Turlings, Ted; Kenis, Marc (My University, 2010)
1. The horse-chestnut leaf miner Cameraria ohridella is an invasive moth in Europe and a serious pest of horse-chestnut Aesculus hippocastanum. The moth also occasionally attacks sycamore maple Acer pseudoplatanus, when situated beside infested horse-chestnuts.
2. The main objective of the present study was to provide an overview of the relationship between C. ohridella and A. pseudoplatanus and to determine whether C. ohridella has the potential to shift to this native tree.
3. In the field, females oviposit on different deciduous tree species. Although less frequently attacked than A. hippocastanum, A. pseudoplatanus was clearly preferred for oviposition over 12 other woody species investigated.
4. Surveys in Europe demonstrated that the majority of A. pseudoplatanus trees found beside infested A. hippocastanum had mines of C. ohridella, even though more than 70% of the larvae died within the first two instars. Attack rates and development success greatly varied from site to site. Attack levels on A. pseudoplatanus were not always correlated with those on A. hippocastanum, and mines on A. pseudoplatanus were sometimes observed beside weakly-infested A. hippocastanum.
5. Field observations, experimental exposure of A. pseudoplatanus saplings and rearing trials in a common garden study showed that individual trees may vary in their susceptibility to C. ohridella, whereas there was no evidence that C. ohridella populations vary in their performance on A. pseudoplatanus.
6. To date, there is little evidence that C. ohridella represents a major risk for A. pseudoplatanus.
Keywords: Acer pseudoplatanus; Cameraria ohridella; ecological impact; host shift; invasive alien insect; leaf miner